Statistical Analysis of Financial Results of Organizations in the Russian Federation ("Journal "U". Economy. Management. Finance.", 2020)
This article examines the trend of financial results of organizations of the Russian Federation, except for small businesses, for the period 2002-2020. The analysis of the influence of various factors on the financial result of organizations is carried out. It is revealed that the dollar exchange rate has the strongest impact.